Pharmacotherapy of Primary Impulsive Aggression in Violent Criminal Offenders - Felthous, Alan R.; McCoy, Bridget; Nassif, Jose Bou; Duggirala, Rajat; Kim, Ellen; Carabellese, Fulvio; Stanford, Matthew S. (Frontiers in Psychology, 2021)
Primary impulsive aggression (PIA) can be implicated as a common factor that results in arrest, disciplinary and restraint measures during confinement, and criminal recidivism after release. Evidence suggests that anti-impulsive aggression agents (AIAAs) can diminish or prevent impulsive aggression even when occurring with personality pathology such as borderline or antisocial personality disorder, common conditions in offender populations. A previous review identified agents that have been subjected to controlled drug trials of sufficient quality, and subsequently a decisional algorithm was developed for selecting an AIAA for individuals with IA. This selection process began with the five agents that showed efficacy in two or more quality studies from the earlier review. Today, eight years after the quality review study, the present authors undertook this follow up literature review. The aims of the present review were to survey the literature to identify and assess: 1) drug trials of comparable quality published since the 2013 review, including trials of the previously identified AIAAs as well as trials of agents not included in the earlier review; 2) severity of aggressive outbursts; 3) the materiality of risks or side-effects that are associated with individual AIAAs as well as antipsychotic agents commonly used to control clinical aggression; 4) efficacy of these agents in special populations (e.g., females,) and 5) cost and convenience of each agent. Improved pharmacotherapy of PIA by addressing risks, side effects and practicality as well as efficacy of AIAAs, should promote the rehabilitation and reintegration of some pathologically aggressive offenders back into the community.